Absolute quantification of Dehalococcoides proteins: enzyme bioindicators of chlorinated ethene dehalorespiration - Jeffrey J. Werner; A. Celeste Ptak; Brian G. Rahm; Sheng Zhang; Ruth E. Richardson (Environmental Microbiology, 2009)
Summary The quantification of trace proteins in complex environmental samples and mixed microbial communities would be a valuable monitoring tool in countless applications, including the bioremediation of groundwater contaminated with chlorinated solvents. Measuring the concentrations of specific proteins provides unique information about the activity and physiological state of organisms in a sample. We developed sensitive ( Dehalococcoides spp. when reducing carbon atoms in the common pollutants trichloroethene (TCE) and tetrachloroethene (PCE). From complex whole‐sample digests of two different dechlorinating mixed communities, we monitored the chromatographic peaks of selected tryptic peptides chosen to represent 19 specific Dehalococcoides proteins. This was accomplished using multiple‐reaction monitoring (MRM) assays using nano‐liquid chromatography‐tandem mass spectrometry (nLC‐MS/MS), which provided the selectivity, sensitivity and reproducibility required to quantify Dehalococcoides proteins in complex samples. We observed reproducible peak areas (average CV = 0.14 over 4 days, n = 3) and linear responses in standard curves ( n = 5, R 2 > 0.98) using synthetic peptide standards spiked into a background matrix of sediment peptides. We detected and quantified TCE reductive dehalogenase (TceA) at 7.6 ± 1.7 × 10 3 proteins cell −1 in the KB1 TM bioaugmentation culture, previously thought to be lacking TceA. Fragmentation data from MS/MS shotgun proteomics experiments were helpful in developing the MRM targets. Similar shotgun proteomics data are emerging in labs around the world for many environmentally relevant microbial proteins, and these data are a valuable resource for the future development of MRM assays. We expect targeted peptide quantification in environmental samples to be a useful tool in environmental monitoring.